Implementation of the Sipraja Program in Public Administrative Services - Suhartatik, Maria Anis; Rodiyah, Isnaini (Indonesian Journal of Public Policy Review, 2024)
General background: Efficient public administration in village governance is key to improving community services. Specific background: The Siwalanpanji Village Government has implemented the Sipraja program, aiming to enhance population administration services. Knowledge gap: Despite the use of Sipraja, challenges remain in budget allocation, communication, and operator motivation, suggesting the need for evaluation to determine its effectiveness. Aims: This study analyzes the implementation of the Sipraja program in Siwalanpanji Village using Edward III’s policy theory framework, focusing on communication, resources, disposition, and bureaucratic structure. Results: The findings reveal that communication has been effectively facilitated by village officials who guide residents in using the application. Resources are adequate in terms of facilities, and officials can operate Sipraja, though budget sources remain unfulfilled as a motivator for operators. The disposition aspect is positive, with policymakers’ commitment aligning with existing regulations. The bureaucratic structure is relatively efficient, supported by clear standard operating procedures. However, the need for community socialization and consistent financial support is evident. Novelty: This study provides a detailed evaluation of Sipraja's implementation in administrative services, highlighting communication and resource gaps that affect the program's effectiveness. Implications: The study emphasizes the importance of financial support and community socialization for successful digital administration services in village governance. Highlights: Effective communication is crucial for successful digital service implementation in village governance. Resource gaps, including budget constraints, impact the program's operator motivation. Clear standard operating procedures support a more efficient bureaucratic structure. Keywords: Implementation, Sipraja Application, Population Administration, Village Governance, Digital Systems